2014
DOI: 10.1007/s00704-014-1138-7
|View full text |Cite
|
Sign up to set email alerts
|

The Yellow River basin becomes wetter or drier? The case as indicated by mean precipitation and extremes during 1961–2012

Abstract: The Yellow River basin could be divided into three sub-regions, which makes it as the ideal target for studying regional climate change. On the basis of daily precipitation at 62 meteorological stations in the Yellow River basin, spatial distribution and temporal trends of annual and monthly mean precipitation and extremes were analyzed during 1961-2012. The Mann-Kendall trend test and linear least-square method were used to detect trends and magnitudes in annual and monthly mean precipitation and extremes. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 54 publications
2
19
1
1
Order By: Relevance
“…Although positive trends in extreme precipitation dominated during the last few decades, these trends were not spatially uniform (Ghosh et al ., ; Liang et al ., ; Song et al ., ). The formation of precipitation is a complex process (Liu et al ., ).…”
Section: Resultsmentioning
confidence: 77%
See 1 more Smart Citation
“…Although positive trends in extreme precipitation dominated during the last few decades, these trends were not spatially uniform (Ghosh et al ., ; Liang et al ., ; Song et al ., ). The formation of precipitation is a complex process (Liu et al ., ).…”
Section: Resultsmentioning
confidence: 77%
“…Gemmer et al (2011) found that annual Mx1day in the Pearl River basin increased at only 6% of stations at the 0.1 significance level. In the Yellow River basin, situated in northern YRB, only 1.6% of stations measured increasing Mx1day trends at the 0.05 significance level (Liang et al, 2015). In the Songhua River basin in Northeastern China, no stations showed significant Mx1day trends (Song et al, 2015).…”
Section: Observed Trends In Annual and Seasonal Mx1day Using The Mk Testmentioning
confidence: 98%
“…Linear regression analysis was used to analyze the trends and variation rate of hydrological and meteorological variables in different periods [59]. The slope of the linear regression equation is regarded as the variation rate during the specific period [60][61][62]. The significance of the correlation can be determined by the size of the Pearson correlation coefficient.…”
Section: Statistical Methods For Trend Analysis and Correlation Analysismentioning
confidence: 99%
“…Furthermore, studies have noted variations in extreme precipitation that may lead to local flooding over short periods of time, resulting in tremendous economic loss. In general, extreme precipitation is defined as annual total precipitation with daily precipitation > 95th percentile, named P95, which is one of the thirteen extreme precipitation indices introduced by the ETCCDI (the Expert Team on Climate Change Detection and Indices) [10,11]. Recent research indicates that extreme precipitation in Xinjiang also exhibits increasing trends [12][13][14][15][16], consistent with regional and global studies [17][18][19].…”
Section: Introductionmentioning
confidence: 99%